Pengaruh Gaya Kepemimpinan Terhadap Perilaku Kinerja Guru SDIT Ishlahul Ummah Kota Sawahlunto - Takwim, Takwim; Hendriani, Suswati (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
This article analyzes the impact of Leadership Style on Teacher Performance Behavior at SDIT Ishlahul Ummah, Sawahlunto City. The focus is on the six main leadership styles, namely transformational, transactional, autocratic, charismatic, bureaucratic and democratic. This article has provided deep insight into leadership styles; democratic, transformational, bureaucratic and autocratic leadership have a positive impact on the performance of SDIT Ishlahul Ummah teachers in Sawahlunto City. This article uses analysis of primary data and secondary data that has been carried out. The analysis uses a quantitative approach, with the help of survey instruments, based on a questionnaire survey. Secondary research has been carried out through a review of previous literature set out to achieve the research objectives. The results of this article suggest that charismatic, bureaucratic and transactional leadership styles have a negative relationship with performance. Transformational, autocratic, and democratic leadership styles, on the other hand, have a positive relationship with teacher performance at SDIT Ishlahul Ummah, Sawahlunto City.